Prevalence Of Tuberculin Skin Test Positivity In Patients Of Early Rheumatoid Arthritis- Study from a tertiary care centre in North India. - Dr. Kriti Kishor; Dr. Debashish Mishra; Dr. Siddharth Jain; Dr. Nusrat Shafiq; Dr. Varun Dhir; Dr. Sanjay Jain; Dr. Shefali K Sharma (International Journal of Medical Research and Review, 2021)
Objective: To assess the prevalence of tuberculin skin test (TST) positivity in early rheumatoid arthritis patients (< 6months disease duration) using Tuberculin sensitivity testing in a TB endemic country.Method: Included in this cross-sectional study were 200 patients of early rheumatoid arthritis divided into three groups- treatment naïve, patients on methotrexate only and methotrexate plus low dose corticosteroids.Results: 200 early RA patients and 60 healthy controls were included in this study. The median age of the study population was 43 years (IQR 33-51) with a mean disease duration of 3.4 ± 2.1 months. 54 patients (27%) with early RA and 22 healthy control (36.7%) had TST positive (p=0.1).Conclusion: Tuberculin positivity is low among patients with early RA as compared to the general population. The use of low dose steroids or methotrexate doesn’t affect the tuberculin anergy.